THE INFLUENCE OF SELF-REGULATED LEARNING AND PEER ENVIRONMENT ON ACADEMIC PROCRASTINATION STUDENTS - Iwangga, Silvia; Sri Arita (JURNAL PENDIDIKAN GLASSER, 2025)
This study was motivated by the importance of understanding and addressing students' tendency to deliberately and continuously procrastinate in completing academic assignments, which affects learning outcomes and can lead to the development of maladaptive habits over time. The objective of this study is to analyze the influence of self-directed learning and peer social environment on academic procrastination among Economics Education students at the Faculty of Economics and Business, University of Padang. This study employs a quantitative methodology with a causal design. Data were collected using a structured questionnaire. The population in this study consists of Economics Education students at the Faculty of Economics and Business, University of Padang. The sample consisted of 209 participants selected through proportional random sampling. The coefficient of determination obtained in this study was 12.3%, indicating that self-directed learning and peer social environment contribute to academic procrastination, while the remaining percentage is explained by factors outside the scope of this study. This research contributes to the development of educational psychology by highlighting the importance of self-regulation skills and social environments in addressing academic procrastination among university students.